2020
DOI: 10.1016/j.ijbiomac.2020.04.095
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and adhesive properties of multilayered coatings based on catechol-functionalized chitosan/hyaluronic acid and bioactive glass nanoparticles

Abstract: Chitosan and hyaluronic acid are the most attractive natural polysaccharides used for tissue regeneration, herein innovative orthopedic coatings were constructed by dip-coating technique. Inspired by the tough nacre-like structure, multifunctional (MF) films were constructed using bioactive glass nanoparticles (BGNPs) as the inorganic phase and hyaluronic acid (HA) and chitosan (CHT) polymers as the organic phase. Polymeric (CTR) films were also built with both polysaccharides. Inspired by the marine mussel's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…Hyaluronic acid (HA), widely found in the extracellular matrix, is a naturally occurring acidic GAG. HA plays an essential role in inflammation, angiogenesis, and tumour microenvironment formation, which is therefore widely used in tissue engineering, soft tissue fillers, wound dressings, and other biomedical applications [87][88][89][90][91]. Sulphated GAGs, such as chondroitin sulphate, heparan sulphate, are found in the tissues of terrestrial and marine animals (e.g., intestinal mucosa, lungs, blood vessel walls, skin, bones, etc.)…”
Section: Marine Glycosaminoglycansmentioning
confidence: 99%
“…Hyaluronic acid (HA), widely found in the extracellular matrix, is a naturally occurring acidic GAG. HA plays an essential role in inflammation, angiogenesis, and tumour microenvironment formation, which is therefore widely used in tissue engineering, soft tissue fillers, wound dressings, and other biomedical applications [87][88][89][90][91]. Sulphated GAGs, such as chondroitin sulphate, heparan sulphate, are found in the tissues of terrestrial and marine animals (e.g., intestinal mucosa, lungs, blood vessel walls, skin, bones, etc.)…”
Section: Marine Glycosaminoglycansmentioning
confidence: 99%
“…Using freeze induced assembly and hot-pressing methods, Chen et al [ 49 ] toughened and modified delignificated nano-cellulose (DNLC) by the synergistic effect of CS and MoS 2 and prepared the high-performance ternary lignocellulose nacres. Additionally, Almeida et al [ 50 ] proposed multifunctional (MF) CS/hyaluronic acid (HA) LbL films developed by the dip-coating technology. They alternately combined the inorganic nanoparticles and bioactive glass nanoparticles (BGNP) with catechol-functionalized biopolymeric layers CS and HA to obtain MF films, which could be used in bone tissue engineering because of their ability to create an environment compatible with osteogenesis ( Figure 6 ).…”
Section: Biomaterials Imitating Bivalvesmentioning
confidence: 99%
“… Schematic illustration of the different multifunctional (MF) and control (CTR) LbL coatings (11×: the number of repetitions required for the CTR group to alternately immerse the substrate in the oppositely-charged polyelectrolyte solutions to produce LbL coatings with 11 bilayers, i.e., 22 layers; 5×: the number of repetitions required for the MF group to alternately immerse the substrate in the oppositely-charged polyelectrolyte solutions to produce LbL coatings with 22 layers). Reproduced with permission from [ 50 ], Copyrighter Elsevier 2020. …”
Section: Figurementioning
confidence: 99%
“…The adhesive properties of such conjugates were combined with antimicrobial and bioactive properties of Ag-doped bioglass nanoparticles for the fabrication of multifunctional biocomposites, which were prepared by LBL assembly for application in orthopedic implants [ 138 ]. Catechol-modified HYH was also combined with catechol-modified chitosan for the fabrication of advanced multilayer bioactive films containing bioglass or Ag-doped bioglass [ 139 , 140 , 141 ]. Due to the use of catechol-modified polymers, the films showed enhanced adhesion to the substrates [ 139 ].…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%
“…Catechol-modified HYH was also combined with catechol-modified chitosan for the fabrication of advanced multilayer bioactive films containing bioglass or Ag-doped bioglass [ 139 , 140 , 141 ]. Due to the use of catechol-modified polymers, the films showed enhanced adhesion to the substrates [ 139 ]. Additionally, Moreira et al reported that incorporation of catechol groups into the films showed a significant increase in the films’ stiffness and lower swelling [ 140 ].…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%